71 A genome-wide association study in Indian Asians identifies four susceptibility loci for type-2 diabetes. (9th June 2011) - Sehmi, J; Salaheen, D; Yeo, Y; Zhang, W; Das, D; McCarthy, M I; Tai, E S; Danesh, J; Kooner, J; Chambers, J
Abstract : Background: Type-2 diabetes (T2D) is a major risk factor for cardiovascular disease, and a leading causing of mortality worldwide. T2D is 2–4 fold more common among Indian Asians than Europeans, and contributes to higher cardiovascular disease mortality in Asians. Little is known of the genetic basis of T2D in Indian Asians. Methods: We carried out a genome-wide association (GWA) study of T2D in 5561 Indian Asian cases and 14 458 controls from LOLIPOP, PROMIS and SINDI cohorts. Whole genome scans were performed using the Illumina 317 k or 610 k arrays. Further testing of suggestive SNPs was carried out in independent cohorts of Indian Asian (12 K T2D cases and 25 K controls) and European ancestry (DIAGRAM+, 8 K T2D cases and 39 K controls). Results: There were two novel loci associated with T2D at p<10 −6, and an additional 57 loci associated with T2D at p<10 −4 in the GWA study. We used results from DIAGRAM+ to prioritise 19 loci for further testing in Indian Asians. In combined analysis of results from GWA and further testing, four loci now reached genome-wide significance (p<5×10 −8 ) among Indian Asians. Coding variant and eQTL studies at these loci identify genes closely involved in insulin secretion and signalling. Conclusion: We identify four novel genetic loci associated with T2D in Indian Asians. Our observations provide new insights into the biological mechanisms underlying T2D, a major risk factor for cardiovascular disease.